A Review of Eudemian Ethics by Aristotle - Houriye Bakouei Ketrimi; Hassan Fathi (پژوهش‌نامۀ انتقادی متون و برنامه‌های علوم انسانی)
This article reviews and criticizes Aristotle’s Eudemian Ethics based on Anthony Kenny’s translation. We have tried to show that morality in Aristotle means living good, and his purpose in writing this work is to find an answer to the question “ what is good life and how can we achieve it?”; an answer in the virtuous tradition of the philosophical environment about which he is thinking. Hence, the understanding of the nature of what happiness is based on the understanding of the nature of virtue is significant. After examining all the various virtues, he ultimately defines happiness as “full life activity according to complete virtues” (1219 a, 39), and this main virtue includes all other virtues, namely moral virtue and intellectual virtue. Studying and acquainting with such a book for those interested in ethical studies have this advantage that they can examine some of the ethical issues in society from the scope of virtuosity.